2014
DOI: 10.5114/wiitm.2014.45048
|View full text |Cite
|
Sign up to set email alerts
|

Image-based guidance of percutaneous abdomen intervention based on markers for semi-automatic rigid registration.

Abstract: IntroductionFor percutaneous abdomen intervention (e.g. liver radiofrequency (RF) tumor ablation, liver biopsy), surgeons lack real-time visual feedback about the location of the needle on planning images, typically computed tomography (CT). One difficulty lies in tracking and synchronizing both the tool movement and the patient breathing motion.AimTo verify the correspondence between rigid registration fiducial registration error signal and breathing phase.Material and methodsDesigned markers that are clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The tracking of markers attached to the breathing part of the patient can produce surrogate breathing signal [7]. The previous worked [8,9] showed that could be useful for real-time comparison online patient breathing phase and phase estimation from CT images. …”
Section: Resultsmentioning
confidence: 99%
“…The tracking of markers attached to the breathing part of the patient can produce surrogate breathing signal [7]. The previous worked [8,9] showed that could be useful for real-time comparison online patient breathing phase and phase estimation from CT images. …”
Section: Resultsmentioning
confidence: 99%